Food Cravings and the Effects of Left Prefrontal Repetitive Transcranial Magnetic Stimulation Using an Improved Sham Condition - Barth, Kelly; Rydin-Gray, Sofia; Kose, Samet; Borckardt, Jeffrey; O'Neil, Patrick; Shaw, Darlene; Madan, Alok; George, Mark (Frontiers in Psychiatry, 2011)
This study examined whether a single session of repetitive transcranial magnetic stimulation (rTMS) of the left prefrontal cortex would inhibit food cravings in healthy women who endorsed frequent food cravings. Ten participants viewed images of food and completed ratings for food cravings before and after receiving either real or sham rTMS over the left prefrontal cortex (10Hz, 100% rMT, 10 seconds-on, 20 seconds-off for 15 minutes; 3000 pulses). Sham TMS was matched with real TMS with respect to perceived painfulness of the stimulation. Each participant received both real and sham rTMS in random order and were blind to the condition in a within-subject cross-over design. With an improved sham control condition, prefrontal rTMS inhibited food cravings no better than sham rTMS. The mild pain from the real and sham rTMS may distract or inhibit food craving, and the decreased craving may not be caused by the effect of rTMS itself. Further studies are needed to elucidate whether rTMS has any true effects on food craving and whether painful stimuli inhibit food or other cravings. A sham condition which matches the painfulness is important to understand the true effects of TMS on behaviors and diseases.